2013
DOI: 10.1089/thy.2012.0416
|View full text |Cite
|
Sign up to set email alerts
|

Association of Socioeconomic Status with Iodine Supply and Thyroid Disorders in Northeast Germany

Abstract: Socioeconomic status neither substantially influences iodine supply nor does it have a major impact on the prevalence and incidence of thyroid deficiency-related disorders in the adult population of northeast Germany, indicating a good efficacy of the German iodine fortification program in all socioeconomic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 34 publications
(24 reference statements)
0
14
0
1
Order By: Relevance
“…Even in other developed countries where health is a concerning public issue, myths have led to non-usage of iodized food products. In some European populations, such as Germany, groups argue against iodine fortification because of putative risks of allergies, skin disorders, and cancer, neglecting dose-response relationships between iodine use and such disorders 75 . In other countries, including the United Kingdom 76 and the United States, 1 salt intake is reduced because of potential risks of cardiovascular health, which subsequently leads to suboptimal iodine intake.…”
Section: Discussionmentioning
confidence: 99%
“…Even in other developed countries where health is a concerning public issue, myths have led to non-usage of iodized food products. In some European populations, such as Germany, groups argue against iodine fortification because of putative risks of allergies, skin disorders, and cancer, neglecting dose-response relationships between iodine use and such disorders 75 . In other countries, including the United Kingdom 76 and the United States, 1 salt intake is reduced because of potential risks of cardiovascular health, which subsequently leads to suboptimal iodine intake.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that severe ID is particularly prevalent in poor and less-educated people living in less-developed countries. Education has been shown to be a strong predictor of iodine intake levels (9) at both the population and individual level. For example, in 2000, the Belgium population began to consume more foods with iodine, resulting in a silent prophylaxis process, even before the salt iodization program was implemented (10), or as documented at the individual level in Indonesian (11), African (8), and Asian populations (12) where the mother's education is the strongest predictor of inadequately low iodine intake in children from urban slums and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…The intersectoral approach may include promoting the right to education; ensuring appropriate access to water, sanitation, and hygiene (WASH); promoting employability; and ensuring human security and coordination with social protection. For instance, accumulating evidence shows that mothers’ education is a critical determinant for the adoption of a health intervention and that poor WASH conditions affect the absorption of certain micronutrients, decreasing the effectiveness of food fortification in certain settings . A comprehensive, equity‐sensitive approach should also include coordination with policies on noncommunicable diseases, including those related to the reduction of salt intake.…”
Section: Other Considerations On Social Determinants Of Health and Inmentioning
confidence: 99%